eXistenZ: “terroristi e nuovi realisti”: Osservazioni fenomenologiche sul rapporto illusione-realtà nel cinema e nella realtà virtuale - Taddio, Luca (Scenari, 2021)
This essay aims at examining the perception of virtual reality starting from the analysis of the relationship between a direct perceptive experience of the film image and the appearance-reality dichotomy. The connection between image and reality will be considered as a “phenomenon” of the experienced reality. This appearance could be understood in terms which are not properly “subjective”. The cinematographic image is considered as a virtual look at the reality of the visible. The essay would like to show some possible research guidelines which are meant to focus on cinema according to a “realist” perspective and a methodology which is in line with the ecological approach by James J. Gibson, with the experimental phenomenology by Paolo Bozzi, and the philosophy of “New Realism”.